2021
DOI: 10.1371/journal.pntd.0009692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between blood hemoglobin concentration determined by point-of-care device and complete blood count in adult patients with dengue

Abstract: Background Hematocrit measurement has been an indispensable tool for monitoring plasma leakage and bleeding in dengue patients. However, hematocrit measurement by automated methods is hampered by frequent venipunctures. Utility of point-of-care hemoglobin (POC-Hb) test for monitoring dengue patients has not been established. We evaluated the relationship between hemoglobin measured by POC-Hb testing and hematocrit measured by the automated method in adult dengue patients. Methodology and principal findings A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 11 Thrombocytosis is a condition in which a high platelet count (>450,000/μL) causes inappropriate blood coagulation. 12 In this study, 33.33% of NS1- and dengue IgM-reactive patients had a platelet count of less than 100,000/μL, and the rest 66.66% had a platelet count of more than 100,000/μL. The mean platelet count in reactive patients was found to be 138,033/μL in male patients and 143,315.8/μL in female patients.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“… 11 Thrombocytosis is a condition in which a high platelet count (>450,000/μL) causes inappropriate blood coagulation. 12 In this study, 33.33% of NS1- and dengue IgM-reactive patients had a platelet count of less than 100,000/μL, and the rest 66.66% had a platelet count of more than 100,000/μL. The mean platelet count in reactive patients was found to be 138,033/μL in male patients and 143,315.8/μL in female patients.…”
Section: Discussionmentioning
confidence: 49%
“…An inadequate platelet count can lead to two different conditions: thrombocytopenia: a low platelet count (<150,000/μL) can cause excessive bleeding and bruising . Thrombocytosis is a condition in which a high platelet count (>450,000/μL) causes inappropriate blood coagulation . In this study, 33.33% of NS1- and dengue IgM-reactive patients had a platelet count of less than 100,000/μL, and the rest 66.66% had a platelet count of more than 100,000/μL.…”
Section: Discussionmentioning
confidence: 62%
“…The hemoconcentration phenomenon is present in many clinical scenarios such as induced hemorrhage, 13 exercise, 14 and heat stress 15 among many others. However, in the specific context of hemodialysis, there is lack of a validated gold standard or substantial consensus regarding the proper strategy to deal with hemoconcentration, leading to the indistinct use of outdated correction factors in modern studies.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in platelet count and HCT values are primary manifestations in dengue patients and are associated with the severity of the disease 29 . The HCT elevation is a feature associated with systemic capillary leak and is also considered an essential diagnostic parameter for the determination of plasma leakage prompted by cytokine‐mediated alterations in vascular permeability before the onset of severe DHF/DSS 30,31 . Several pieces of evidence have reported that the decreased platelet count, raised HCT, and altered coagulation profile significantly influenced the dengue severity.…”
Section: Discussionmentioning
confidence: 99%
“…29 The HCT elevation is a feature associated with systemic capillary leak and is also considered an essential diagnostic parameter for the determination of plasma leakage prompted by cytokine-mediated alterations in vascular permeability before the onset of severe DHF/DSS. 30,31 Several pieces of evidence have reported that the decreased platelet count, raised HCT, and altered coagulation profile significantly influenced the dengue severity. In an experimental study involving 105 dengue-affected pediatric population, it was reported that DHF/DSS condition was associated with a severe decline in platelet count (<20,000/mm 3 ) in comparison to DF subjects who had mild to moderate thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%